Lymphocyte metabolism and the level of circulatory cytokines in children with autoimmune disease - T. V. Radygina; O. V. Kurbatova; D. G. Kuptsova; S. V. Petrichuk; A. P. Fisenko; G. B. Movsisyan; L. M. Abdullaeva; A. S. Potapov; N. N. Murashkin; D. V. Parakhina (Медицинская иммунология, 2024)
In recent decades, there has been an increase in the incidence of autoimmune diseases (AID) among adults and children. The immunopathogenesis of AID is based on an imbalance between autoaggressive and regulatory cells (Tregs), which is regulated by metabolic signaling pathways and the cytokine microenvironment. Understanding the mechanisms of immunometabolism opens up new possibilities for the treatment of patients with AID. The aim was to evaluate the activity of lymphocyte dehydrogenases associated with OXPHOS and glycolysis, depending on the level of proinflammatory and anti-inflammatory cytokines in children with AID.324 children with AID were examined: 80 – Crohn’s disease (CD), 53 – ulcerative colitis (UC), 89 – psoriasis (PS), 66 – multiple sclerosis (MS), 36 – autoimmune hepatitis (AIH). Activity of mitochondrial dehydrogenases (succinate dehydrogenase (SDH) and glycerol-3-phosphate dehydrogenase (GFDH)) were evaluated by immunocytochemical method using flow cytometry. The level of cytokines (CС) in blood sera was determined by multiplex analysis.In each studied group of children, CС with the highest values in exacerbation and remission of the disease were identified. The maximum values of CС were in patients with exacerbation: CD, UC, PS, MS – IL-23; AIH – IL-27. Evaluation of cytokine complexes associated with cells showed significant differences between patients in exacerbation/remission: CD, UC and PS – M1(IL-1+IL-6+TNFα), cTh1(IFNγ+IL-12p70+TNFβ+IL-2), cTh2 (IL-4+IL-5+IL-10+IL-13+IL-17E/IL-25+IL-33), cTh17 (IL-1β+IL-6+IL-17A+IL-17F+IL-21+IL-22+IL-23); MS – M1, cTh1, cTh2; AIH – cTh2. SDH activity in AID remission differed between pathologies in CD4+ cells, Th17 and Tregs. In exacerbation of AID, there were differences in Tregs between patients with UC and PS. The highest GPDH activity in exacerbation was observed in CD4+ lymphocytes, Th17 and Tregs in CD. The ratio of SDH/GPDH in T-lymphocytes in children with CD in exacerbation and remission was lowest and significantly lower than in UC, PS, MS, AIH and apparently healthy children. In the group of children with a low SDH/GPDH ratio, the levels of CCL20/MIP3α, IFNγ, IL-12p70, IL-13, IL-17A, IL-1β, and TNFα were significantly increased. Conclusions. Informative cytokine complexes were identified in children with AID. The relationship between the metabolic activity of lymphocytes and the level of circulating cytokines is shown.